Interconnection between Globalization and Foreign Direct Investment in Africa - Souleymane Diarra; Andrey V. Girinsky (RUDN Journal of Economics)
Foreign direct investment (FDI) is an important source of capital inflows to many African countries. Despite the marked improvement in economic, political, and social conditions in these capital-scarce countries, foreign investors do not consider them viable locations to locate in the country. Since FDI brings huge spillovers to the host country, some countries have recently institutionalized globalization as a catalyst to reverse this trend. Against this background, the relationship between FDI and globalization in African countries in recent years is examined. Using an extended panel estimation, the results show that FDI into Africa is indeed driven by globalization. Moreover, it is clear that this positive relationship is due to the economic dimension of globalization. Overall, the potential of globalization to stimulate an FDI boom in Africa has been demonstrated. The relationship between globalization and foreign direct investment (FDI) in Africa is multifaceted and plays a crucial role in the economic development of the continent. Globalization, characterized by the acceleration of trade, capital movements and increased interconnection between countries, has opened up new opportunities for Africa. The FDI, which refers to investments made by foreign companies in productive assets in a host country, is a key vector of this dynamic. At the same time, many African countries face a number of challenges associated with FDI inflows, such as the need to improve infrastructure, improve legal frameworks and reduce corruption. Thus, to maximize the benefits of globalization and attract more FDI, African countries need to continue reforms and strengthen their institutional environment. This will not only increase economic growth, but also increase resilience to external shocks and improve the overall stability of the economy in the region, which will further increase FDI.